PARADIGMA BARU PENDIDIKAN ISLAM DALAM UPAYA MENJAWAB TANTANGAN GLOBAL - Hanafy, Muh Sain (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2017)
The problems faced by education nowadays in imple-mentation teaching and learning prosess is the failure of Islamic edu-cation occuring in Islamic instution. This is because of the application of education which is merely concentrating on cognitive aspect including the willingness to apply the value of Islamic teaching. The development of Islamic education must rely on new paradigms that education has appreciation to democracy, individual differences, equality, diversity and involving society in decision making toward policy of education.